2021
DOI: 10.1093/nop/npab002
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic neurological syndrome: an evolving story

Abstract: Paraneoplastic neurological syndrome (PNS) comprises a group of neurological disorders that result from a misguided immune response to the nervous system triggered by a distant tumor. These disorders frequently manifest before the diagnosis of the underlying neoplasm. Since the first reported case in 1888 by Oppenheim, the knowledge in this area has evolved rapidly. Several classic PNS have been described, such as limbic encephalitis, paraneoplastic cerebellar degeneration, encephalomyelitis, opsoclonus-myoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 141 publications
0
16
0
1
Order By: Relevance
“…[ 12 ] found that among 14 cases who had spontaneously regressed lung carcinoma were patients with PNS, some who were positive for onconeural antibodies. PNS is among a group of neurological disorders [13] triggered by a distant tumor and not directly caused by cancer metastasis, side effects of cancer treatment, nutritional deficiencies, metabolic derangements, or coagulopathies [14] . PNS arises in the context of an immune response generated against antigens expressed on tumor cells that are also expressed in the nervous system [15] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] found that among 14 cases who had spontaneously regressed lung carcinoma were patients with PNS, some who were positive for onconeural antibodies. PNS is among a group of neurological disorders [13] triggered by a distant tumor and not directly caused by cancer metastasis, side effects of cancer treatment, nutritional deficiencies, metabolic derangements, or coagulopathies [14] . PNS arises in the context of an immune response generated against antigens expressed on tumor cells that are also expressed in the nervous system [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple PNSs are induced by immune reactions, which frequently manifest as antineuronal antibodies measurable in serum and cerebrospinal fluid ( 6 ). The onconeural antibodies typically associated with PCD include Purkinje cytoplasmic antibody 1 (PCA-1, Yo), Purkinje cytoplasmic antibody Tr (PCA-Tr, Tr) and metabotropic glutamate receptor 1 (mGluR1) ( 7 ). The presence of antibodies against intracellular onconeural autoantibodies highly suggests an underlying tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features encompass brainstem encephalitis, cerebellar degeneration, myelitis and/or sensory and autonomic neuropathies. Multifocal syndromes without encephalitis, including myeloneuropathy and paraneoplastic-subacute-combined degeneration, would also fall under this broad category [ 34 ]. The most common underlying malignancy is SCLC.…”
Section: Approach To the Selection Of Paraneoplastic Neurologic Syndr...mentioning
confidence: 99%
“…The most commonly associated malignancy is SCLC (70–80% of cases) [ 44 ]. Common onconeural antibodies associated with this disorder include: anti-Hu, amphiphysin, CRMP5 and PCA2 antibodies [ 34 ]. Prompt treatment with corticosteroids may help to improve the sensory deficit [ 45 ].…”
Section: Approach To the Selection Of Paraneoplastic Neurologic Syndr...mentioning
confidence: 99%